Exploitation-exploration balance and its performance outcomes: A study of FDI portfolio decisions of new multinationals - Piotr Trąpczyński; Tilo F. Halaszovich (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to explore how new multinationals construct their FDI location portfolios and what the performance outcomes of these decisions are. Research Design & Methods: Building our conceptual framework on the organisational learning theory, we conduct regression analysis based on data from 394 subsidiaries of new Polish multinationals. Findings: We find that the possession of superior capabilities by new multinationals enhances their ability to reap benefits from investing in more advanced markets in their portfolios and hence engaging in higher ambidexterity, i.e. the combination of exploration and exploitation. This effect is further reinforced by experience with foreign investment. Implications & Recommendations: Investment in more advanced economies as compared to the home country entails the possession of higher-order capabilities, as it requires higher ambidexterity from new multinationals. Contribution & Value Added: A lot of existing IB research focused on discrete location choices in internationalisation, remaining oblivious of the broader strategic logic. Moreover, it has been assumed that - particularly for new multinationals from emerging countries - entries into advanced host countries are related to exploration rather than exploitation, whereby the latter is the domain of similar or less developed markets.
Keywords: F23; L25; M16; 330; new multinationals; location choices; portfolio perspective; firm capabilities; firm performance; Central and Eastern Europe